Evaluation of Response to Complexity (R2C) - Harris, Lyndsey (University of Nottingham, 2016)
This is a mixed-methods evaluation of a Department of Communities and Local Government (DCLG) funded coordinated response to support survivors of domestic and sexual abuse with complex needs (mental ill-health, substance misuse including alcohol and/or dual diagnosis) in Nottingham.